ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEIKUTSERTAANSENAM HAMIL PADA IBU HAMIL TRIMESTER III DI BPM HJ. DINCE SAFRINA SST - Wiwi Sartika; Siti Qomariah (LPPM Universitas Abdurrab, 2019)
Pregnancy and childbirth are natural processes for a woman, during pregnancy the body will experience many adaptations of physiology and psychology. Physiological adaptation consists of changes in the reproductive system, changes in the cardiovascular system, changes in the respiratory system, changes in the gastrointestinal system, changes in the renal system, changes in the endocrine system, changes in the abdominal wall and skin, and metabolic changes while psychological changes consist of stressors during pregnancy and changes in pregnancy . The purpose of this study is to determine the analysis of factors that influence the participation of pregnancy exercise in trimester III pregnant women at the BPM Hj. Dince Safrina, SST. The research used was quantitative observational analytic (cross-sectional) with elements of independent and dependent variables. The population in this study were all mothers - third trimester pregnant women (gestational age above 28 weeks) who visited the BPM Hj. Dince Safrina, SST. Samples with a sample of 61 respondents. Sampling is done in Accidental Sampling. Data used are primary data by distributing questionnaires. Data analysis was done by univariate, bivariate with chi-square test and multivariate with multiple logistic regression tests. The results of the multivariate analysis variables that most influenced the participation of pregnant gymnastics were the motivation variable (OR: 6.93; 95% CI: 1.95-24.60). The conclusion in this study is that high motivation from both pregnant women and families 6.93 times affected pregnant women to take part in pregnancy exercises at the nearest health facility.